THE IMPACT OF OUTPUT STRUCTURE AND NOMINAL CONVERGENCE ON REAL CONVERGENCE: THE CASE OF BULGARIA - Todorov, . Ivan; Stavrova, Elena (Revista Inclusiones, 2021)
The goal of this paper is to analyze the influence of output structure similarity and nominal convergence on real convergence between Bulgaria and the Euro area. The objective of the research is achieved by applying an autoregressive distributed lag (ARDL) approach on quarterly seasonally adjusted Eurostat data for the period 2003-2020. The empirical results indicate the existence of a long-run equilibrium relationship between real convergence, nominal convergence and output structure. The catch-up process of Bulgaria with the Euro area is affected by the differences in household consumption (in the short term) and government debt (both in the short run and in the long-term) between the two entities. Since the economic parameters in the Euro area are beyond the reach of Bulgaria’s macroeconomic management, Bulgarian policymakers can encourage real convergence of Bulgaria to the Euro area by increasing the share of government debt in GDP and by stimulating Bulgarian households to decrease the share of their consumption in GDP